Identification, cDNA cloning, and gene expression of soluble starch synthase in rice (Oryza sativa L.) immature seeds. - Baba, T (1993)
Three forms of soluble starch synthase were resolved by anion-exchange chromatography of soluble extracts from immature rice (Oryza sativa L.) seeds, and each of these forms was further purified by affinity chromatograph. The 55-, 57-, and 57-kD proteins in the three preparations were identified as candidates for soluble starch synthase by western blot analysis using an antiserum against rice granule-bound starch synthase. It is interesting that the amino-terminal amino acid sequence was identical among the three proteins, except that the 55-kD protein lacked eight amino acids at the amino terminus. Thus, these three proteins are products of the same gene. The cDNA clones coding for this protein have been isolated from an immature rice seed library in lambda gt11 using synthetic oligonucleotides as probes. The deduced amino acid sequence of this protein contains a lysine-X-glycine-glycine consensus sequence for the ADP-glucose-binding site of starch and glycogen synthases. Therefore, we conclude that this protein corresponds to a form of soluble starch synthase in immature rice seeds. The precursor of the enzyme contains 626 amino acids, including a 113-residue transit peptide at the amino terminus. The mature form of soluble starch synthase shares a significant but low sequence identity with rice granule-bound starch synthase and Escherichia coli glycogen synthase. However, several regions, including the substrate-binding site, are highly conserved among these three enzymes. Blot hybridization analysis demonstrates that the gene encoding soluble starch synthase is a single-copy gene in the rice genome and is expressed in both leaves and immature seeds. These results suggest that soluble and granule-bound starch synthases play distinct roles in starch biosynthesis of plant.